Pre-Requisites of Pre-Service Secondary Teacher Education Programme in Jharkhand: An Analysis - Shilpi Kumari; Subhash Chandra Panda (Journal of Education and Learning (EduLearn), 2013)
The fundamental basis of the curriculum, critical andragogical input, availability of time period, modern and innovative transactional approaches and qualitative evaluation process in the prescribed curriculum, infrastructural facilities as well as the teacher composition are considered to be the quality indicators of teacher education programme. The study was delimited to colleges (both private and government) having attached B.Ed. wing under Kolhan University. By utilizing both qualitative and quantitative techniques the relevant data were collected in terms of intended curriculum, infrastructural facilities and teacher composition. Subsequently it was revealed that the secondary teacher education programme of Kolhan University was more or less a knowledge transmission model inefficient to foster prospective teachers as a facilitator of pupil’s learning in varied socio-cultural contexts. The present research contrives necessary measures to evolve a quality teacher education programme which may be capable of meeting the emerging challenges of secondary education in Jharkhand.